Hydrophilic self-cleaning glaze, hydrophilic self-cleaning archaized brick and preparation method of hydrophilic self-cleaning archaized brick

By applying hydrophilic self-cleaning glaze containing fluxes such as boric acid and lithium carbonate on the surface of antique bricks, a glaze layer that is resistant to aging and high binding force is formed, the problem of poor self-cleaning in the prior art is solved, and antique is realized The bricks have a lasting self-cleaning effect and reduce production costs.

CN119143391AActive Publication Date: 2024-12-17FOSHAN DONGPENG CERAMIC +3

Patent Information

Application Number
CN202411258365.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-17
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

The hydrophilic self-cleaning coatings of existing antique bricks have poor aging resistance and limited binding power, resulting in poor self-cleaning aging, and the additional coating of hydrophilic self-cleaning coatings is not conducive to reducing production costs.

Method used

Use a hydrophilic self-cleaning glaze formula, including 75-95% hydrophilic fuses and 5-25% kaolin, and form a partial melt through fluxes such as boric acid, lithium carbonate, wollastonite, and burnt talc. After calcination, Combined with high-temperature raw materials, a glaze layer that is resistant to aging and high binding force is directly glazed on the surface of antique bricks.

Benefits of technology

It realizes the durable self-cleaning of antique bricks, improves aging resistance and bonding, reduces production costs, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005034768940000111
    Figure BDA0005034768940000111
Patent Text Reader

Abstract

The invention discloses a hydrophilic self-cleaning glaze which comprises the following components in percentage by mass: 75-95% of hydrophilic frit and 5-25% of kaolin, the hydrophilic frit comprises the following components in percentage by mass: 2-4% of boric acid, 5-9% of lithium carbonate, 30-40% of wollastonite, 9-16% of calcined talc, 10-20% of kaolin, 13-22% of quartz and 8-12% of aluminum oxide. According to the hydrophilic self-cleaning glaze provided by the invention, on the premise of reducing the production cost, excellent and lasting self-cleaning performance can be realized, and the technical problem of poor timeliness of self-cleaning performance in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building ceramics, in particular to a hydrophilic self-cleaning glaze, a hydrophilic self-cleaning antique brick and a preparation method thereof. Background Art

[0002] Antique tiles, as an artistic building material that combines classical aesthetics with modern craftsmanship, are deeply favored by consumers for their unique antique glaze effect, rich color layers and strong historical charm. They are widely used in home decoration, commercial places, cultural and tourist attractions and other fields.

[0003] In order to ensure the antique effect of antique tiles, the surface of antique tiles is usually designed to be uneven. Although the uneven surface of antique tiles is conducive to increasing their anti-slip performance, it is also easy to become a breeding ground for dirt and grime, which not only affects the aesthetics of antique tiles and reduces their decorative effect, but also makes the dirt treatment of antique tiles time-consuming and laborious, and requires the help of cleaning agents to effectively remove dirt.

[0004] In order to overcome the above-mentioned defects, the prior art usually coats the surface of the antique brick with a hydrophilic self-cleaning coating, so that a layer of hydrophilic self-cleaning coating is formed on the surface of the antique brick, so that water can spread quickly when it contacts the coating surface (i.e., the static contact angle between water and the coating is small) and form a uniform water film, which can penetrate into the interface between the dirt and the coating, thereby weakening the adhesion of the dirt, and under the action of gravity, the continuously flowing water film can take away and remove the dirt on the surface of the antique brick, achieving the effect of self-cleaning. However, due to the poor aging resistance of the hydrophilic self-cleaning coating and its limited bonding force with the brick surface, the hydrophilic self-cleaning coating is easy to fall off, the service life is extremely limited, and the self-cleaning durability is poor, which cannot meet the actual use requirements. At the same time, additionally coating the surface of the antique brick substrate with a hydrophilic self-cleaning coating is not conducive to reducing production costs. Summary of the invention

[0005] The purpose of the present invention is to provide a hydrophilic self-cleaning glaze, which can achieve excellent and lasting self-cleaning performance under the premise of reducing production costs, and solve the technical problem of poor timeliness of self-cleaning performance in the prior art.

[0006] The second purpose of the present invention is to provide a method for preparing a hydrophilic self-cleaning antique tile. The preparation method is simple and easy to operate, ensuring that the obtained hydrophilic self-cleaning antique tile not only has excellent and lasting self-cleaning properties, but also helps to reduce costs.

[0007] The third object of the present invention is to provide a hydrophilic self-cleaning antique tile prepared by the above-mentioned method for preparing the hydrophilic self-cleaning antique tile, which has excellent and lasting self-cleaning performance.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] A hydrophilic self-cleaning glaze, calculated by mass percentage, comprises 75-95% of hydrophilic frit and 5-25% of kaolin;

[0010] Calculated by mass percentage, the hydrophilic frit includes 2-4% boric acid, 5-9% lithium carbonate, 30-40% wollastonite, 9-16% calcined talc, 10-20% kaolin, 13-22% quartz and 8-12% alumina.

[0011] Furthermore, calculated by mass ratio, the ratio of the sum of the mass percentages of the boric acid and the lithium carbonate to the sum of the mass percentages of the wollastonite and the calcined talc is 1:(4-7).

[0012] Furthermore, calculated by mass percentage, the hydrophilic frit includes 3% boric acid, 8% lithium carbonate, 35% wollastonite, 12% calcined talc, 15% kaolin, 17% quartz and 10% alumina.

[0013] A method for preparing a hydrophilic self-cleaning glaze antique tile, using the hydrophilic self-cleaning glaze, comprises the following steps:

[0014] A. Mix boric acid, lithium carbonate, wollastonite, calcined talc, kaolin, quartz and alumina uniformly according to the proportion, calcine and then quench with water to obtain a hydrophilic frit;

[0015] B. After kaolin and the hydrophilic frit of step A are uniformly mixed according to the proportion, sodium carboxymethyl cellulose, sodium tripolyphosphate and water are added for ball milling, and the mixture is sieved to obtain a hydrophilic self-cleaning glaze;

[0016] C. Apply the hydrophilic self-cleaning glaze of step B to the body with concave-convex effect, dry and calcine to obtain the hydrophilic self-cleaning antique tile.

[0017] Furthermore, in step A, the calcination curve of the hydrophilic frit is: heating from room temperature to 1530° C. at a heating rate of 8 to 10° C. / min, and then keeping the temperature for 35 to 45 minutes.

[0018] Furthermore, in step B, the specific gravity of the hydrophilic self-cleaning glaze is 1.82 to 1.9.

[0019] Furthermore, according to mass percentage, the residue of the hydrophilic self-cleaning glaze passing through a 325-mesh sieve is 0.2-0.4%.

[0020] Furthermore, in step C, the glazing thickness of the hydrophilic self-cleaning glaze is 0.3-0.7 mm.

[0021] Furthermore, in step C, the calcination temperature is 1200-1220°C.

[0022] A hydrophilic self-cleaning antique brick is prepared using the above-mentioned method for preparing the hydrophilic self-cleaning antique brick.

[0023] The technical solution provided by the present invention may include the following beneficial effects:

[0024] 1. In the early stage of firing, the hydrophilic frit formula system has achieved phase separation, and boric acid and lithium carbonate form the phase-separated upper layer, and the second gradient fluxing system (wollastonite and calcined talc) and high-temperature raw materials (kaolin, quartz and alumina) form the phase-separated lower layer. When the temperature reaches the melting point of each raw material in the lower layer, the raw materials in the lower layer will gradually melt. At the same time, as the calcination temperature continues to rise, the raw materials in the phase-separated upper layer and the phase-separated lower layer will gradually decompose, so that the hydrophilic frit will eventually form a phase-separated melt with boron oxide and lithium oxide as the phase-separated upper layer, and calcium oxide, magnesium oxide, aluminum oxide and silicon oxide as the phase-separated lower layer. When the hydrophilic frit, which is essentially a phase-separated melt, is added to the glaze formula, the glaze is calcined to form a glaze layer with boron oxide and lithium oxide as the phase-separated upper layer, and calcium oxide, magnesium oxide, aluminum oxide and silicon oxide as the phase-separated lower layer.

[0025] 2. Compared with the hydrophilic self-cleaning coating, the aging resistance of the hydrophilic self-cleaning glaze layer is greatly improved, which is conducive to overcoming the technical defects of the prior art that the hydrophilic self-cleaning coating has poor aging resistance and poor self-cleaning timeliness. In addition, since the hydrophilic self-cleaning glaze layer is directly calcined by the hydrophilic self-cleaning glaze, it has a very high bonding force with the antique brick, which is conducive to overcoming the technical defects of the prior art that the hydrophilic self-cleaning coating has limited bonding force with the brick surface of the antique brick, resulting in poor self-cleaning timeliness. The mutual coordination of the above-mentioned multiple factors is conducive to achieving the long-lasting self-cleaning of the antique brick, and the self-cleaning is excellent. In addition, the technical solution does not need to additionally coat the surface of the antique brick with a hydrophilic self-cleaning coating, which is conducive to saving production costs and improving production efficiency.

[0026] 3. The introduction of boric acid not only promotes the phase separation of the hydrophilic self-cleaning glaze during the calcination process, but also helps to inhibit the crystallization between the two phase separation melts of the upper phase separation layer and the lower phase separation layer of the hydrophilic self-cleaning glaze during the calcination process, thereby preventing the liquid phase of the upper phase separation layer from being too low, resulting in unstable hydrophilic properties of the hydrophilic self-cleaning glaze. DETAILED DESCRIPTION

[0027] The technical solution provides a hydrophilic self-cleaning glaze, which comprises 75-95% of hydrophilic frit and 5-25% of kaolin, calculated by mass percentage;

[0028] Calculated by mass percentage, the hydrophilic frit includes 2-4% boric acid, 5-9% lithium carbonate, 30-40% wollastonite, 9-16% calcined talc, 10-20% kaolin, 13-22% quartz and 8-12% alumina.

[0029] The prior art usually applies a hydrophilic self-cleaning coating on the surface of the antique brick substrate, so that a layer of hydrophilic self-cleaning coating is formed on the surface of the antique brick, so that even if there is dirt on the surface of the antique brick, the dirt can be easily removed. However, due to the poor aging resistance of the hydrophilic self-cleaning coating and its limited bonding with the brick surface, the hydrophilic self-cleaning coating is easy to fall off, the service life is extremely limited, and the hydrophilic self-cleaning durability is poor, which cannot meet the actual use requirements. At the same time, additionally applying a hydrophilic self-cleaning coating on the surface of the antique brick substrate is not conducive to reducing production costs.

[0030] In order to achieve long-lasting self-cleaning properties under the premise of reducing costs, the technical solution proposes a hydrophilic self-cleaning glaze, the raw materials of which include hydrophilic frit and kaolin. Among them, the hydrophilic frit uses boric acid, lithium carbonate, wollastonite and calcined talc as fluxes, and the melting point of boric acid is about 577°C, the melting point of lithium carbonate is about 723°C, the melting point of wollastonite is about 1500°C, and the melting point of calcined talc is about 1400°C, so that the hydrophilic frit formula forms a first gradient fluxing system composed of boric acid and lithium carbonate, and a second gradient fluxing system composed of wollastonite and calcined talc, and the melting temperatures of the two gradient fluxing systems are extremely different. At the same time, the melting temperature of the first gradient fluxing system and the high-temperature raw materials (i.e., raw materials forming the solid phase) in the hydrophilic frit formula, such as kaolin, quartz and alumina, differs greatly, and the melting temperature of the high-temperature raw materials in the second gradient fluxing system and the hydrophilic frit formula differs less, so that in the early stage of firing, the first gradient fluxing system melts first, and the melt obtained by calcining the hydrophilic frit in the early stage of calcination is mainly boric acid and lithium carbonate. As the calcination temperature increases, the melt viscosity gradually decreases, and other raw materials that are far from reaching the melting point, such as the second gradient fluxing system and the high-temperature raw materials, will sink. That is, in the early stage of firing, the hydrophilic frit formula system has achieved phase separation, and boric acid and lithium carbonate form a phase-separated upper layer, and the second gradient fluxing system (wollastonite and calcined talc) and the high-temperature raw materials (kaolin, quartz and alumina) form a phase-separated lower layer. When the temperature reaches the melting point of each raw material in the lower layer, each raw material in the lower layer will also gradually melt. At the same time, as the calcination temperature continues to rise, the raw materials in the phase-separated upper layer and the phase-separated lower layer will gradually decompose, so that the hydrophilic frit will eventually form a phase-separated melt with boron oxide and lithium oxide as the phase-separated upper layer and calcium oxide, magnesium oxide, aluminum oxide and silicon oxide as the phase-separated lower layer. When the hydrophilic frit, which is essentially a phase-separated melt, is added to the glaze formula, the glaze is calcined to form a glaze layer with boron oxide and lithium oxide as the phase-separated upper layer and calcium oxide, magnesium oxide, aluminum oxide and silicon oxide as the phase-separated lower layer.

[0031] Furthermore, since the surface tension of lithium oxide is 450×10 -3 N / M, the surface tension of boron oxide is 80×10 - 3 N / M, while the surface tension of water is 73×10 -3N / m, that is, the surface tension of the glaze layer is much greater than the surface tension of water, so that the glaze layer is essentially a hydrophilic self-cleaning glaze layer with extremely strong hydrophilic properties on the surface, so that even if the surface of the glaze layer is adhered with dirt, the dirt is relatively easy to remove. At the same time, compared with the hydrophilic self-cleaning coating, the aging resistance of the hydrophilic self-cleaning glaze layer is greatly improved, which is conducive to overcoming the technical defects of poor self-cleaning timeliness due to the poor aging resistance of the hydrophilic self-cleaning coating in the prior art. In addition, since the hydrophilic self-cleaning glaze layer is directly calcined by the hydrophilic self-cleaning glaze, its bonding force with the antique brick is extremely high, which is conducive to overcoming the technical defects of limited bonding force between the hydrophilic self-cleaning coating and the brick surface of the antique brick in the prior art, resulting in poor self-cleaning timeliness. The mutual coordination of the above multiple factors is conducive to realizing the long-lasting self-cleaning of the antique brick, and the self-cleaning is excellent. In addition, the technical solution does not need to additionally apply a hydrophilic self-cleaning coating on the surface of the antique brick, which is conducive to saving production costs and improving production efficiency.

[0032] Furthermore, the introduction of boric acid in the present technical scheme not only promotes the phase separation of the hydrophilic self-cleaning glaze during the calcination process, but also helps to inhibit the crystallization of the hydrophilic self-cleaning glaze between the two phase-separated melts of the upper phase-separated layer and the lower phase-separated layer during the calcination process, thereby preventing the liquid phase of the upper phase-separated layer from being too low, resulting in unstable hydrophilic properties of the hydrophilic self-cleaning glaze.

[0033] It should be further explained that the prior art generally adds potassium feldspar and sodium feldspar to the hydrophilic frit, and the melting point of potassium feldspar is about 1150°C and the melting point of sodium feldspar is about 1120°C. When potassium feldspar and sodium feldspar are added to the hydrophilic frit formula, the melting temperature difference between the first gradient fluxing system and the second gradient fluxing system will be greatly reduced, resulting in the inability of the formula system to achieve phase separation. At the same time, since potassium feldspar and sodium feldspar contain a large amount of aluminum oxide and silicon dioxide components, the high-temperature viscosity of the early melt will not drop significantly, further resulting in the inability of the formula system to achieve phase separation. In addition, the potassium oxide produced during the calcination of potassium feldspar and the sodium oxide produced during the calcination of sodium feldspar have a surface tension smaller than that of water, that is, when potassium feldspar and sodium feldspar are added to the formula, it is not conducive to the self-cleaning property of the glaze. Therefore, the hydrophilic frit containing potassium feldspar and sodium feldspar as fluxes cannot be added to the present technical solution.

[0034] Furthermore, the kaolin, quartz and alumina in the hydrophilic frit are not only conducive to improving the hardness, wear resistance and other properties of the hydrophilic frit, but the above three raw materials are all high-temperature raw materials, which are conducive to increasing the temperature difference between the upper raw materials and the lower raw materials in the hydrophilic frit, and promoting phase separation in the early stage of firing. It should be noted that the kaolin in the hydrophilic self-cleaning glaze formula of the technical solution is mainly used as a suspending agent to prevent the hydrophilic frit from settling and affecting its performance.

[0035] Furthermore, the hydrophilic frit includes 2-4% boric acid, 5-9% lithium carbonate, 30-40% wollastonite, 9-16% calcined talc, 10-20% kaolin, 13-22% quartz and 8-12% alumina, calculated by mass percentage. That is, the ratio of the sum of the mass percentages of boric acid and lithium carbonate to the sum of the mass percentages of wollastonite and calcined talc is 1:(3-8). When the ratio of the sum of the mass percentages of boric acid and lithium carbonate to the sum of the mass percentages of wollastonite and talc is greater than 1:3, the amount of liquid phase formed by boric acid and lithium carbonate in the melt in the early stage of calcination will be too much, the fluxing effect will be too strong, and the solid phase raw materials that are difficult to melt in the early stage will be easily melted, resulting in difficulty in phase separation; when the ratio of the sum of the mass percentages of boric acid and lithium carbonate to the sum of the mass percentages of wollastonite and talc is less than 1:8, the amount of liquid phase formed by boric acid and lithium carbonate in the melt in the early stage of calcination will be too small, which will make it difficult for the second gradient fluxing system and high-temperature raw materials to sink, resulting in difficulty in phase separation; on the other hand, it will cause the liquid phase in the upper layer of the phase separation to be too thin, affecting the surface tension of the glaze, and thus affecting its self-cleaning hydrophilic properties.

[0036] It is further described that, calculated by mass ratio, the ratio of the sum of the mass percentages of the boric acid and the lithium carbonate to the sum of the mass percentages of the wollastonite and the calcined talc is 1:(4-7).

[0037] In a preferred embodiment of the present technical solution, by optimizing the ratio of the sum of the mass percentages of boric acid and lithium carbonate to the sum of the mass percentages of wollastonite and talc, it is beneficial to promote the phase separation of the hydrophilic self-cleaning glaze in the early stage of calcination, thereby ensuring the performance of the hydrophilic self-cleaning glaze.

[0038] It is further explained that, calculated by mass percentage, the hydrophilic frit includes 3% boric acid, 8% lithium carbonate, 35% wollastonite, 12% calcined talc, 15% kaolin, 17% quartz and 10% alumina.

[0039] In a preferred embodiment of the present technical solution, by limiting the addition amount of each raw material in the hydrophilic frit, it is helpful to optimize the performance of the hydrophilic frit, thereby helping to ensure the performance of the hydrophilic self-cleaning glaze.

[0040] A method for preparing a hydrophilic self-cleaning glaze antique tile, using the hydrophilic self-cleaning glaze, comprises the following steps:

[0041] A. Mix boric acid, lithium carbonate, wollastonite, calcined talc, kaolin, quartz and alumina uniformly according to the proportion, calcine and then quench with water to obtain a hydrophilic frit;

[0042] B. After kaolin and the hydrophilic frit of step A are uniformly mixed according to the proportion, sodium carboxymethyl cellulose, sodium tripolyphosphate and water are added for ball milling, and the mixture is sieved to obtain a hydrophilic self-cleaning glaze;

[0043] C. Apply the hydrophilic self-cleaning glaze of step B to the body with concave-convex effect, dry and calcine to obtain the hydrophilic self-cleaning antique tile.

[0044] The technical solution also proposes a method for preparing a hydrophilic self-cleaning glaze antique tile, which has simple steps and strong operability, ensuring that the obtained hydrophilic self-cleaning antique tile not only has self-cleaning performance, but also helps to reduce costs.

[0045] Specifically, in step B, calculated by the mass percentage of the dry material of the hydrophilic self-cleaning glaze, the added amount of sodium carboxymethyl cellulose is 0.2%, the added amount of sodium tripolyphosphate is 0.3%, and the added amount of water is 35-38%. After adding the above additives to the mixed material, ball milling is performed for 12 hours, and then sieving is performed to obtain the hydrophilic self-cleaning glaze.

[0046] Further, in step A, the calcination curve of the hydrophilic frit is: heating from room temperature to 1530° C. at a heating rate of 8 to 10° C. / min, and then keeping the temperature for 35 to 45 minutes.

[0047] In a preferred embodiment of the present technical solution, the calcination curve of the hydrophilic frit is optimized so that all the raw materials in the hydrophilic frit formula can be melted, which is conducive to promoting phase separation, ensuring the performance of the hydrophilic frit, and making the hydrophilic self-cleaning glaze with the addition of the hydrophilic frit have a certain sense of transparency after calcination, thereby improving its permeability.

[0048] Further description, in step B, the specific gravity of the hydrophilic self-cleaning glaze is 1.82-1.9.

[0049] When the specific gravity of the hydrophilic self-cleaning glaze is too high, the glaze will be too thick and the fluidity will deteriorate, which will make the application uniformity of the hydrophilic self-cleaning glaze poor and easily form defects such as glaze roads. In addition, the high specific gravity of the hydrophilic self-cleaning glaze will easily hinder the discharge of gas and water generated by the hydrophilic self-cleaning glaze during the calcination process, causing the glaze layer obtained by calcining the hydrophilic self-cleaning glaze to crack easily. When the specific gravity of the hydrophilic self-cleaning glaze is too low, the fluidity of the hydrophilic self-cleaning glaze is too good, and it is easy to flow during the glazing process, which also causes the application uniformity of the hydrophilic self-cleaning glaze to be poor, and it is easy to form defects such as glaze roads. In addition, the specific gravity of the hydrophilic self-cleaning glaze is too low, resulting in excessive water in the glaze, and the phenomenon of brick explosion is easy to occur during the calcination process. It should be noted that the glaze road refers to the glaze layer being thicker in some areas and thinner or missing in other areas.

[0050] Further, in step B, the residue of the hydrophilic self-cleaning glaze passing through a 325-mesh sieve is 0.2-0.4% by mass.

[0051] In a preferred embodiment of the present technical solution, by limiting the fineness of the hydrophilic self-cleaning glaze, the sieve residue of the hydrophilic self-cleaning glaze is relatively low, which is beneficial for making the hydrophilic self-cleaning glaze have fine uniformity, reducing the rough glaze surface caused by uneven particles, and improving the self-cleaning performance.

[0052] Further, in step C, the glazing thickness of the hydrophilic self-cleaning glaze is 0.3-0.7 mm.

[0053] In a preferred embodiment of the present technical solution, by limiting the glazing thickness, it is beneficial to have a certain thickness of the melt mainly composed of boric acid and lithium carbonate in the early stage of calcination, so that the raw materials that have not yet reached the melting point have enough space to sink, thereby promoting phase separation and ensuring its performance.

[0054] Further, in step C, the calcination temperature is 1200-1220°C.

[0055] In a preferred embodiment of the present technical solution, by limiting the glaze firing temperature to 1200-1220°C, which is consistent with the firing temperature of existing antique tile products, it is easy to achieve the purpose of industrialized production while ensuring product performance and reducing large deviations between the experimental stage and the industrialization stage.

[0056] A hydrophilic self-cleaning antique brick is prepared using the above-mentioned method for preparing the hydrophilic self-cleaning antique brick.

[0057] A hydrophilic self-cleaning antique tile prepared by the preparation method of the hydrophilic self-cleaning antique tile has excellent and lasting self-cleaning performance.

[0058] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0059] Performance Test:

[0060] Static contact angle before immersion: According to the test method of GB / T 30447-2013 Nanofilm Contact Angle Measurement Method, the static contact angle of the hydrophilic self-cleaning antique tile before immersion in boiling water is tested. If the static contact angle is <15°, it is qualified.

[0061] Static contact angle after immersion: According to the test method of "GB / T 30447-2013 Nanofilm Contact Angle Measurement Method", the hydrophilic self-cleaning antique tiles are tested for their static contact angle after being immersed in boiling water for 30 days. If the contact angle is less than 25°, it is qualified.

[0062] Anti-slip performance: Anti-slip performance is tested according to the DIN 51130:2014 anti-slip standard.

[0063] Mohs hardness: The Mohs hardness of the hydrophilic self-cleaning antique tile is tested using a Mohs hardness tester.

[0064] Example 1

[0065] A. According to the mass percentage, 3% boric acid, 8% lithium carbonate, 35% wollastonite, 12% calcined talc, 15% kaolin, 17% quartz and 10% alumina are mixed evenly, calcined and then water quenched to obtain a hydrophilic frit; wherein the calcination curve of the hydrophilic frit is: from room temperature to 1530°C at a heating rate of 8-10°C / min, and then kept warm for 40 minutes;

[0066] B. Calculated by mass percentage, 20% of kaolin and 80% of the hydrophilic frit of step A are uniformly mixed, sodium carboxymethyl cellulose, sodium tripolyphosphate and water are added for ball milling, and sieved to obtain a hydrophilic self-cleaning glaze with a specific gravity of 1.82; wherein, by mass percentage, the residue of the hydrophilic self-cleaning glaze passing through a 325-mesh sieve is 0.2%; calculated by mass percentage of the dry material of the hydrophilic self-cleaning glaze, the addition amount of sodium carboxymethyl cellulose is 0.2%, the addition amount of sodium tripolyphosphate is 0.3%, and the addition amount of water is 35%;

[0067] C. Apply the hydrophilic self-cleaning glaze of step B to the body with concave-convex effect, dry and calcine at a temperature of 1200-1220° C. to obtain the hydrophilic self-cleaning antique tile; wherein the glazing thickness of the hydrophilic self-cleaning glaze is 0.5 mm.

[0068] Example 2

[0069] A. According to the mass percentage, 2% of boric acid, 9% of lithium carbonate, 30% of wollastonite, 16% of calcined talc, 20% of kaolin, 15% of quartz and 8% of alumina are mixed evenly, calcined and then quenched with water to obtain a hydrophilic frit; wherein the calcination curve of the hydrophilic frit is: from room temperature to 1530°C at a heating rate of 8-10°C / min, and then kept warm for 35 minutes;

[0070] B. Calculated by mass percentage, 10% of kaolin and 90% of the hydrophilic frit of step A are uniformly mixed, and then sodium carboxymethyl cellulose, sodium tripolyphosphate and water are added for ball milling, and sieved to obtain a hydrophilic self-cleaning glaze with a specific gravity of 1.85; wherein, by mass percentage, the residue of the hydrophilic self-cleaning glaze passing through a 325-mesh sieve is 0.3%; calculated by mass percentage of the dry material of the hydrophilic self-cleaning glaze, the addition amount of sodium carboxymethyl cellulose is 0.2%, the addition amount of sodium tripolyphosphate is 0.3%, and the addition amount of water is 38%;

[0071] C. Apply the hydrophilic self-cleaning glaze of step B to the body with concave-convex effect, dry and calcine at a temperature of 1200-1220° C. to obtain the hydrophilic self-cleaning antique tile; wherein the glazing thickness of the hydrophilic self-cleaning glaze is 0.3 mm.

[0072] Example 3

[0073] A. According to the mass percentage, 4% boric acid, 5% lithium carbonate, 40% wollastonite, 9% calcined talc, 17% kaolin, 13% quartz and 12% alumina are mixed evenly, calcined and then quenched with water to obtain a hydrophilic frit; wherein the calcination curve of the hydrophilic frit is: from room temperature to 1530°C at a heating rate of 8-10°C / min, and then kept warm for 45 minutes;

[0074] B. Calculated by mass percentage, 10% of kaolin and 90% of the hydrophilic frit of step A are uniformly mixed, sodium carboxymethyl cellulose, sodium tripolyphosphate and water are added for ball milling, and sieved to obtain a hydrophilic self-cleaning glaze with a specific gravity of 1.9; wherein, by mass percentage, the residue of the hydrophilic self-cleaning glaze passing through a 325-mesh sieve is 0.4%; calculated by mass percentage of the dry material of the hydrophilic self-cleaning glaze, the addition amount of sodium carboxymethyl cellulose is 0.2%, the addition amount of sodium tripolyphosphate is 0.3%, and the addition amount of water is 35%;

[0075] C. Apply the hydrophilic self-cleaning glaze of step B to the body with concave-convex effect, dry and calcine at a temperature of 1200-1220° C. to obtain the hydrophilic self-cleaning antique tile; wherein the glazing thickness of the hydrophilic self-cleaning glaze is 0.7 mm.

[0076] Comparative Example 1

[0077] The hydrophilic self-cleaning antique brick in Comparative Example 1 includes an antique brick substrate and a hydrophilic self-cleaning coating distributed from bottom to top; wherein the hydrophilic self-cleaning coating is obtained by curing a super hydrophilic coating of model SM-TM-QS3500 / 3200 produced by Shangmeng Technology Wuxi Co., Ltd.

[0078] Comparative Example 2

[0079] Comparative Example 2 has the same preparation method and raw materials as Example 1, except that potassium feldspar and sodium feldspar are added to the hydrophilic frit formula in Comparative Example 2. That is, in Comparative Example 1, the hydrophilic frit includes 3% boric acid, 8% lithium carbonate, 5% potassium feldspar, 3% sodium feldspar, 30% wollastonite, 12% calcined talc, 12% kaolin, 17% quartz and 10% alumina, calculated by mass percentage.

[0080] Comparative Example 3

[0081] The preparation method and raw materials of Comparative Example 3 are the same as those of Example 1, except that in Comparative Example 3, calculated by mass ratio, the ratio of the sum of the mass percentages of boric acid and lithium carbonate to the sum of the mass percentages of wollastonite and talc is 1:2.

[0082] Comparative Example 4

[0083] The preparation method and raw materials of Comparative Example 4 are the same as those of Example 1, except that in Comparative Example 4, the ratio of the sum of the mass percentages of boric acid and lithium carbonate to the sum of the mass percentages of wollastonite and talc is 1:9.

[0084] The performance tests were conducted on the hydrophilic self-cleaning antique tiles prepared by the preparation methods of Examples 1-3 and Comparative Examples 1-4, and the results are shown in Table 1 below:

[0085] Table 1 Performance test results of different hydrophilic self-cleaning antique tiles in the embodiments and comparative examples

[0086]

[0087] It can be seen from the performance test results in Table 1 that the static contact angle of the antique bricks obtained by the present technical solution before immersion is 8-15°, and the static contact angle after immersion is 15-22°. It not only has excellent and lasting self-cleaning performance, but also has good anti-slip properties and hardness, and is both decorative and practical, which is more conducive to meeting the use needs of consumers.

[0088] In Comparative Example 1, a hydrophilic self-cleaning coating is provided on the surface of the antique brick substrate to obtain a hydrophilic self-cleaning antique brick. Although the obtained antique brick has a small static contact angle with water before immersion and has good self-cleaning property, it is affected by the poor aging resistance of the hydrophilic self-cleaning coating and its limited bonding force with the brick surface. As a result, after immersion, the hydrophilic self-cleaning coating of the hydrophilic self-cleaning antique brick in Comparative Example 1 falls off, the hydrophilic self-cleaning durability is poor, and the static contact angle after immersion cannot be measured.

[0089] In Comparative Example 2, since potassium feldspar and sodium feldspar are added to the hydrophilic frit formula, not only does it make phase separation difficult, but it also reduces the surface tension of the glaze layer obtained by calcining the hydrophilic self-cleaning glaze, increases the static contact angle of the antique tile, and reduces its self-cleaning property.

[0090] In Comparative Example 3, since the ratio of the sum of the mass percentages of boric acid and lithium carbonate to the sum of the mass percentages of wollastonite and talc is too large, the amount of liquid phase formed by boric acid and lithium carbonate in the melt in the early stage of calcination is too large, and the fluxing effect is too strong, which easily melts the solid phase raw materials that are difficult to melt in the early stage, resulting in difficulty in phase separation, which increases the static contact angle of the antique tile and reduces its self-cleaning property.

[0091] In Comparative Example 4, since the ratio of the sum of the mass percentages of boric acid and lithium carbonate to the sum of the mass percentages of wollastonite and talc is too small, the amount of liquid phase formed by boric acid and lithium carbonate in the melt in the early stage of calcination is too small. On the one hand, it makes it difficult for the second gradient fluxing system and the high-temperature raw materials to sink, resulting in difficulty in phase separation; on the other hand, it makes the liquid phase in the upper layer of the phase separation too thin, affecting the surface tension of the glaze, and further affecting its self-cleaning hydrophilic properties.

[0092] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A hydrophilic self-cleaning glaze, characterized in that: Calculated by weight percentage, it includes 75-95% of hydrophilic frit and 5-25% of kaolin; Calculated by mass percentage, the hydrophilic frit includes 2-4% boric acid, 5-9% lithium carbonate, 30-40% wollastonite, 9-16% calcined talc, 10-20% kaolin, 13-22% quartz and 8-12% alumina.

2. A hydrophilic self-cleaning glaze according to claim 1, characterized in that: Calculated by mass ratio, the ratio of the sum of the mass percentages of the boric acid and the lithium carbonate to the sum of the mass percentages of the wollastonite and the calcined talc is 1:(4-7).

3. A hydrophilic self-cleaning glaze according to claim 1, characterized in that: Calculated by mass percentage, the hydrophilic frit includes 3% boric acid, 8% lithium carbonate, 35% wollastonite, 12% calcined talc, 15% kaolin, 17% quartz and 10% alumina.

4. A method for preparing a hydrophilic self-cleaning glaze antique tile, characterized in that: Using the hydrophilic self-cleaning glaze as described in any one of claims 1 to 3 comprises the following steps: A. Mix boric acid, lithium carbonate, wollastonite, calcined talc, kaolin, quartz and alumina uniformly according to the proportion, calcine and then quench with water to obtain a hydrophilic frit; B. After kaolin and the hydrophilic frit of step A are uniformly mixed according to the proportion, sodium carboxymethyl cellulose, sodium tripolyphosphate and water are added for ball milling, and the mixture is sieved to obtain a hydrophilic self-cleaning glaze; C. Apply the hydrophilic self-cleaning glaze of step B to the body with concave-convex effect, dry and calcine to obtain the hydrophilic self-cleaning antique tile.

5. The method for preparing a hydrophilic self-cleaning glaze antique tile according to claim 4, characterized in that: In step A, the calcination curve of the hydrophilic frit is: heating from room temperature to 1530° C. at a heating rate of 8 to 10° C. / min, and then keeping the temperature for 35 to 45 minutes.

6. The method for preparing a hydrophilic self-cleaning glaze antique tile according to claim 4, characterized in that: In step B, the specific gravity of the hydrophilic self-cleaning glaze is 1.82-1.

9.

7. The method for preparing a hydrophilic self-cleaning glaze according to claim 4, characterized in that: In step B, the residue of the hydrophilic self-cleaning glaze passing through a 325-mesh sieve is 0.2-0.4% by mass.

8. The method for preparing a hydrophilic self-cleaning glaze according to claim 4, characterized in that: In step C, the glazing thickness of the hydrophilic self-cleaning glaze is 0.3-0.7 mm.

9. The method for preparing a hydrophilic self-cleaning glaze according to claim 4, characterized in that: In step C, the calcination temperature is 1200-1220°C.

10. A hydrophilic self-cleaning antique brick, characterized in that: The hydrophilic self-cleaning antique brick is prepared by the preparation method of any one of claims 4 to 9.

Citation Information

Patent Citations

  • Low-temperature wear-resistant frit, wear-resistant glaze using same and glazed tile

    CN111233327A

  • Dry-grained rock plate and preparation method thereof

    CN112723743A

  • Toughened prestressed building ceramic and preparation method thereof

    CN113264784A

  • Wax glaze, waxy 3D ceramic tile and preparation method of waxy glaze and waxy 3D ceramic tile

    CN114956573A

  • Super-hydrophilic self-cleaning ceramic glaze under response of visible light as well as preparation and application methods of super-hydrophilic self-cleaning ceramic glaze

    CN115072999A

Cited By

  • Hydrophilic self-cleaning glaze, hydrophilic self-cleaning archaized brick and preparation method of hydrophilic self-cleaning archaized brick

    CN120483525A